Commentary: Curbing the Nuisance Bear's Garbage Appetite - George W. Barce (Human-Wildlife Interactions, 2017)
Since the early 1900S, the human population in the United States has more than tripled. Likewise, human interactions with wildlife have also increased exponentially (Conover 1995). Within the range of the American black bear (Ursus americanus), wildlife officials and land managers are often called upon to deal with nuisance bears. The Fall 2008 issue of Human–Wildlife Conflicts (now Human– Wildlife Interactions, ) contained several insightful manuscripts regarding the management of nuisance bears.